Robot Pengukur Arah Kiblat Berbasis Offline Untuk Penyandang Tuna Netra - Ikhsan Mahaendra; Ahmad Adib Rofiuddin (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The Qibla is fundamental in matters of Muslim worship so it needs to be given more attention. This research is intended to design a Qibla robot to determine the Qibla direction for blind people. This research uses research and development research methods, namely, by designing an offline-based robotic Qibla direction measuring device for the blind. This research produced findings in the form of a Qibla measuring tool called